PENERAPAN KOMPETENSI PEDAGOGIS TENAGA PENDIDIK PAUD PADA PENCAPAIAN PERKEMBANGAN BAHASA DAN MATEMATIKA ANAK USIA DINI - Moh. Muzaqi (JIV-Jurnal Ilmiah Visi, 2008)
Some of the teachers’ competencies required in early childhood education are the competencies in pedagogy and andragogy. These competencies deal with teachers’ skill in understanding children’s development, preparing lesson plan, and using the right method and materials suitable to the children’s characteristics. This research was conducted to discover how the teachers using pedagogy competency in language and mathematics in early childhood education. The result of this research was based on parents’ evaluation and observation on their children’s development as they have learned language and mathematics in the early childhood education program.